2020
DOI: 10.5339/qmj.2020.19
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of spontaneous subarachnoid hemorrhage in the state of Qatar

Abstract: Background: Spontaneous subarachnoid hemorrhage (SAH) is one of the significant etiologies for stroke. SAH causes higher morbidity and mortality with loss of productivity, resulting in increased disease burden. Only few studies in Qatar have reported on SAH, and the epidemiological features of SAH and aneurysmal SAH (aSAH) have not been comprehensively studied before in Qatar. Our study aimed to describe the epidemiological profile of patients with SAH and aSAH in the State of Qatar. Methods: We rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Spontaneous non-aneurysmal SAH (NASAH) is relatively uncommon and accounts for approximately 20-30% of all SAH cases [4,5]. Although the clinical outcome and prognosis of NASAH vary considerably due to the diversity of underlying causes and comorbidities, several studies showed that complications, including cerebral vasospasm, occurred less frequently in NASAH compared to aneurysmal SAH [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous non-aneurysmal SAH (NASAH) is relatively uncommon and accounts for approximately 20-30% of all SAH cases [4,5]. Although the clinical outcome and prognosis of NASAH vary considerably due to the diversity of underlying causes and comorbidities, several studies showed that complications, including cerebral vasospasm, occurred less frequently in NASAH compared to aneurysmal SAH [6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Females outnumbered males by 2:1 which also is similar to reports from most studies with a few exceptions like a study from Qatar which reported a preponderance of males (68.7%). [ 12 ]…”
Section: Discussionmentioning
confidence: 99%
“…Autopsy studies have provided information on the incidence of IAs although there may be concerns about the accuracy [29] Ibadan Nigeria 1988-1999 17 1.6 Ohaegbulam [24] Enugu, Nigeria 1974-1977 5 1.7 Ugwuanyi et al [34] Abuja Nigeria 2016-2020 27 6.7 Tokpa et al [33] Abidjan Corte Ivoire 2012-2018 128 18.3 ioub et al [32] Dakar Senegal 2013-2016 129 36.8 Ogenga' o et al [22] Nairobi Kenya 1998-2007 56 6.2 Nabaweesi-Batuka et al [19] Nairobi, Kenya 2010-2014 121 30 El Khamlichi et al [5] Rabat Morocco 1983-1999 200 11.7 Khan et al [12] Quarter 2007-2016 323 32.3 Ramnarayan et al [26] Kozhikode, India 1998-2003 182 36.4 Law et al [16] Hong Kong 2002-2006 135 33.75 van Munster et al [35] Kuopulo Finland 1986-2005 1786 94 van Munster et al [35] Utrecht, Netherlands 1986-2005 1788 94 Korja et al [14] Helsinki, Finland 1995-2009 1993 142.4…”
Section: Does the Study Suggest Low Frequency Of Aneurysms In Enugu?mentioning
confidence: 99%
See 1 more Smart Citation